PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP HASIL BELAJAR SISWA - K. S. K. Wardani; A. N. Rahmatih; N. L. P. N. Sriwarthini; N. Nurwahidah; F. P. Astria (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2020)
This study aims to analyze the differences in learning outcomes between students who study with creative problem-solving learning models and students who study with conventional learning models. This type of research is a quasi-experimental research design with a way of pretest-posttest nonequivalent control group design. The population of this research is all students of class VIII of SMP Negeri 3 Seririt in 2018/2019 academic year consisting of 230 students. Class samples were taken by group random sampling technique. Student learning outcomes data were collected by learning outcomes tests which were analyzed descriptively and ANAKOVA, with hypothesis testing performed at a significance level of 0.05. The results showed there were differences in learning outcomes between students who studied with creative problem-solving learning models and students who learned with conventional learning models. Learning outcomes of students who learn with creative problem-solving learning models are at high qualifications (M = 73.00; SD = 8.30). Learning outcomes of students who learn using conventional learning models are at low qualifications (M = 52.00; SD = 7.60). LSD test results show that the learning outcomes of students who learn with creative problem-solving learning models are higher than conventional learning models (F=10,320; p<0,05).